THE EFFECT OF INQUIRY LEARNING AND PEER TEACHING TOWARD STUDENTS’ LEARNING OUTCOME OF FOREARM PASS VOLLEY BALL FOR SEVENTH GRADE MALE STUDENTS OF SMPN 17 JAMBI - Palmizal A; Alek Octadinata (Journal Physical Education, Health and Recreation, 2019)
This study aimed to influence inquiry learning model and peer teaching towards increasing learning outcomes of forearm pass. The research design used quasi-experimental with two groups pre-test posttest design. The population of this research was students of SMP Negeri 17 Jambi, the sample was the seventh grade. Data were analyzed by analysis of the mean differences using the t-test. The results showed that there was an increase in learning outcomes forearm pass volleyball. In the pre test data, the inquiry method obtained an average of 3.65 points and an average value on the posttest of 3.96 points. Whereas in the pre-test data, the peer test learning model obtained an average of 3.65 points and the average value at the posttest was an average of 3.84 points. Based on the Depedent T calculation, it was known that the significance value of p value is 0.003 with this value smaller than the significance value of the T table, while the rejection limit was 0, 05, so that the alternative hypothesis (Ha) was accepted, there was the effect of learning to forearm pass volleyball using the inquiry model on the results of passing under the male students of seventh grade SMP Negeri 17 Jambi. There was an influence of learning to forearm pass volleyball using a peer teaching model to the results of forearm pass in male students of seventh grade SMP Negeri 17 Jambi.